ANALISIS PEMASARAN JAGUNG DI KABUPATEN LABUHANBATU SELATAN - Rahmanta Ginting (Quantitative Economics Journal, 2016)
Marketing on corn trends to concentration and distribute where both of commodities produced in many places in raw materials needs, continiuty of the commodities processing in the low volume to cover costs in marketing in function . Corn marketing the concertration shorts from gathering the agriculture of product from farmers to gatherers, stock gatheres and by trades and ends in distribution case. It works from agents, retailer to consument. The study aims to identify how the marketing line of corn and share margin of market on every line of marketing: primer and secondary data got from farmer and corn trader. Analyze Methods are marketing line, marketing major , price spread and share margin. The study research resulted that these are two forms of corn marketing, they are: (a) Farmer – trader – gatherer – farm store or retailer – consument, (b) Farmer – farm shop or retailer – consunment. Most of the farmers market the on the first line it’s about 70% and the rest one is about 30% on the second one. Margin profit received by the traders is bigger than received by the farmers, either on the first marketing line or the second one